Overcoming drug resistance with on-demand charged thermoresponsive dendritic nanogels. (January 2017) - Molina, Maria; Wedepohl, Stefanie; Miceli, Enrico; Calderón, Marcelo
Aim: To develop nanogels (NG) able to modulate the encapsulation and release of drugs, in order to circumvent drug resistance mechanisms in cancer cells.Materials & methods: Poly- N -isopropylacrylamide–dendritic polyglycerol NG were semi-interpenetrated with 2-acrylamido-2-methylpropane sulfonic acid or (2-dimethylamino) ethyl methacrylate. Physico-chemical properties of the NGs as well as doxorubicin (DOXO) loading and release were characterized. Drug delivery performance was investigated in vitro and in vivo in a multidrug-resistant tumor model.Results: Both the DOXO loaded semi-interpenetrating polymer network NGs were more efficient in multidrug resistant cancer cell proliferation inhibition studies. In vivo, the DOXO loaded NG semi-interpenetrated with 2-acrylamido-2-methylpropane sulfonic acid was able to overcome drug resistance and reduce the tumor volume to about 25%.Conclusion: The innovative semi-interpenetrating polymer network NGs appear to be promising drug carriers for drug resistant cancer therapy.